Effects of CrMnFeCoNi additions on microstructure, mechanical properties and wear resistance of Ti(C,N)-based cermets - Yang, Shandong (2023)
Ti(C,N)-xCrMnFeCoNi-(15wt.%-x)Ni cermets (x = 0wt.%, 5wt.%, 10wt.%, 15wt.%) were fabricated by low-pressure sintering. Because of the sluggish diffusion effect of high-entropy alloy (HEA), the grain growth of cermets containing HEA binder is inhibited. The FCC binder phases of cermets with CrMnFeCoNi/Ni binders generate a uniform dispersion, motivating to form many complete and moderate rim phases and wet the ceramic particles. Furthermore, the hardness of cermets roughly increases, while the strength and fracture toughness maintain the change tendency of rising the peak and then falling with CrMnFeCoNi additions. Ti(C,N)-5wt.% CrMnFeCoNi-10wt.% Ni cermets obtains a prominent mechanical property combination with hardness of 1646 ± 13.5 HV30, strength of 2181 ± 167.2 MPa and fracture toughness of 9.1 ± 0.11 MPa m1/2. Besides, the cermets containing CrMnFeCoNi/Ni binders obtain reduced friction coefficients and low wear rates at 750 °C compared with Ti(C,N)–Ni cermets and Ti(C,N)-HEA cermets. The superior high-temperature wear resistance is ascribed to the thermal softening resistance of CrMnFeCoNi, strengthening and toughening effect of CrMnFeCoNi/Ni on matrix and the transition of wear mechanism from abrasive wear and the removal of tribochemical layers to the removal of tribochemical layers. The cutting lifetime of cermets containing CrMnFeCoNi/Ni binders is increased by 40%–70% in comparison with Ti(C,N)–Ni cermets during machining 17-4 PH stainless steel. Concisely, Ti(C,N)-based cermets with outstanding mechanical, wear resistance and cutting properties can be obtained by partially replacing Ni with 5–10 wt.% CrMnFeCoNi.